Electronic structures of organometallic complexes of f elements: Part 45. Comparison of phenomenological and calculated crystal field parameters of lanthanide organyls estimated on the basis of simple models - Jank, S; Reddmann, H; Amberger, H.-D (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 1998)
The crystal field (CF) parameters of Nd[N(SiMe 3) 2] 3, (THF) 3Li( μ-Cl)Nd[N(SiMe 3) 2] 3 and Nd[N(SiMe 3) 2] 3(CNC 6H 11) 2 (which are considered as model compounds for the corresponding σ-bonded organometallic complexes with [CH(SiMe 3) 2] − ligands), as well as those of organometallic π complexes of the types (Me 3SiC 5H 4) 3Pr and (C 8H 8)Pr[HB(3,5-Me 2pz) 3], were estimated on the basis of simple model calculations (point charge electrostatic model, simple overlap model, angular overlap model) and were compared with the results of CF calculations adopting the phenomenological model. The comparison suggests that these straightforward model calculations may provide satisfactory CF parameters for σ complexes but give poor results for π complexes of the lanthanides.